Beneficial bacteria for aquaculture: nutrition, bacteriostasis and immunoregulation - C. Wang; J. Chuprom; Y. Wang; L. Fu (John Wiley @ Sons Ltd, 2025)
Despite being the fastest growing sector, the modern aquaculture industry faces serious challenges such as the lack of protein source in feed, the susceptibility to pathogens, and deterioration in quality during culture and storage. Bacterial biomass is considered as a proper protein source for feed, and the beneficial bacterial species protect aquatic animals from infection or reduce spoilage of products. In this review, we summarized the application of beneficial bacteria to aquatic products, focusing mainly on the nutritional, anti-pathogenic, antispoilage and immunoregulatory functions of these bacteria. We then discussed the relationship between beneficial bacteria, intestinal microbiota and host immunity, and the recent progress and drawbacks of the technology.